AB0313 CLINICAL PREDICTORS OF MULTIPLE FAILURES TO BIOLOGICAL THERAPY IN PATIENTS WITH RHEUMATOID ARTHRITIS. (2nd June 2020) - Novella-Navarro, M.; Plasencia, C.; Tornero, C.; Franco Gomez, K. N.; Monjo, I.; Navarro-Compán, V.; Peiteado, D.; Balsa, A.
Abstract : Background: Biological therapies have improved the clinical course and quality of life of Rheumatoid Arthritis (RA) patients. Despite the availability and effectiveness of these treatments, some patients present multiple failures to biologic disease-modifying anti-rheumatic drugs (bDMARDs), constituting a challenge to clinicians. Objectives: To determine the frequency of multiple failure to bDMARDs in RA patients and to identify baseline/early features as possible predictors of multiple failure. Methods: This case-control study involved subjects with RA 1, 2 treated with bDMARDs from the RA-Registry at La Paz Hospital between 2000 and 2019. Patients who presented insufficient response to >3 different bDMARDs or >2 bDMARDs with different mechanism of action were considered Multi-refractory ( MR-patients ). Patients who achieved low disease activity or remission (by DAS-28) with the first bDMARD and maintained it in a follow-up period of at least 5 years were considered non-refractory (NR-patients). For all patients, demographic, clinical characteristics and laboratory parameters were assessed in the database at baseline visit, just prior to start bDMARD for first time and at 6-months visit. Descriptive analysis was performed, and using the "refractory status" as the dependent variable, multiple bivariate logistic regression models were performed to identify which variables should be considered in the multivariate analyses. P<0.05 was considered statistically significant. Odds Ratio (OR) and Confidence Intervals (CI) were calculated. IBM SPSS 21.0 Results: In total, 402 RA patients who had ever received bDMARD treatment were identified. According to pre-established inclusion criteria, 112 patients were included: 41 MR-patients (10%) and 71 NR-patients (18%). No differences in gender, age or age at RA diagnosis were found between both groups. Global time on bDMARD treatment was longer in MR-patients (11.7 vs 9.7 years, p=0.01) and survival on first bDMARD was 4.1±3.4 years, which was decreasing with the successive treatments. In MR-patients, shorter disease duration between RA diagnosis and starting bDMARD (6.9 vs 10.0; p=0.04) and higher number of previous cDMARDs were observed. Also presence of erosions and extra-articular manifestations were more frequent in MR-patients (58.5% vs 25.4%, p=0.03 and 29.3% vs 12.7%, p<0.001 ). Results of variables included in bivariate and multivariate analyses are shown in Table 1 . Finally, factors associated with multi-bDMARDs refractoriness in the multivariate analysis were presence of erosions, earlier age at bDMARD start, higher baseline DAS-28 and especially ΔDAS< 1.2 in the first 6 months of treatment (OR 11.12; 95% CI 3.34-26.82). Conclusion: In our cohort, 10% of patients with RA were observed to have multi-refractoriness to bDMARDs. This study also identified baseline and early clinical characteristics of patients as predictors of multi-refractoriness, especially absence of clinical response during the first 6 months on a first bDMARD. References: [1]Arnett FC. Arthritis Rheum 1988;31:315-24. 2 Aletaha D. Arthritis Rheum. 2010;62:2569-81 Disclosure of Interests: Marta Novella-Navarro: None declared, Chamaida Plasencia: None declared, Carolina Tornero: None declared, Karen Nathalie Franco Gomez: None declared, Irene Monjo: None declared, Victoria Navarro-Compán Consultant of: Abbvie, Lilly, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Lilly, Novartis, Pfizer, UCB, Diana Peiteado: None declared, Alejandro Balsa Grant/research support from: BMS, Roche, Consultant of: AbbVie, Gilead, Lilly, Pfizer, UCB, Sanofi, Sandoz, Speakers bureau: AbbVie, Lilly, Sanofi, Novartis, Pfizer, UCB, Roche, Nordic, Sandoz